2011
DOI: 10.1128/jcm.02538-10
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Locus Variable-Number Tandem-Repeat Analysis Genotyping of Human Brucella Isolates from Turkey

Abstract: Brucellosis is the most common anthropozoonosis, with more than 500,000 cases annually. While the disease was eradicated in the vast majority of industrialized regions around the world, it remains a significant public health concern, mainly in the Mediterranean littoral, the Middle East, the Arabian Peninsula, the Indian subcontinent, Asia, Africa, and Central and South America (19,26).Turkey is a relatively large country in the eastern Mediterranean region, with a geographical surface of 783,562 km 2 , and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 16 publications
8
43
0
Order By: Relevance
“…These findings show that the genotypic variation of Ulanqab isolates was predominantly associated with the highly variable panel 2B loci and to a much lesser extent panel 2A (locus Bruce19 and 21) and panel 1 (loci Bruce 43) loci. In agreement with a previous report (Kilic et al, 2011), this may reflect microevolution through a stepwise mutational event of the most variable loci from a very limited number of ancestors. In addition, there was no clear relationship between biovar and genotype within this B. melitensis population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings show that the genotypic variation of Ulanqab isolates was predominantly associated with the highly variable panel 2B loci and to a much lesser extent panel 2A (locus Bruce19 and 21) and panel 1 (loci Bruce 43) loci. In agreement with a previous report (Kilic et al, 2011), this may reflect microevolution through a stepwise mutational event of the most variable loci from a very limited number of ancestors. In addition, there was no clear relationship between biovar and genotype within this B. melitensis population.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have confirmed that MLVA-16 genotyping results show good correlation with epidemiological data with epidemiologically related isolates displaying identical or very closely related genotypes (Al Dahouk et al, 2007; Nöckler et al, 2009; Kilic et al, 2011; Allen et al, 2015) The current study also confirms the occurrence of multipoint outbreak epidemics and intrafamilial brucellosis. The 11 shared genotypes observed during this analysis pertained to 33 Brucella strains obtained from the same area.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The East Mediterranean cluster contained the majority of the strains isolated in Belgium. Nine of them shared the same MLVA11 genotype (genotype 43) with dozens of strains coming from Turkey as previously described [17] [34]. Few strains with the same MLVA11 genotype come from Syria and Irak [17]; this genotype was also observed in strains coming from Lebanon [35].…”
Section: Discussionmentioning
confidence: 64%
“…Few strains with the same MLVA11 genotype come from Syria and Irak [17]; this genotype was also observed in strains coming from Lebanon [35]. Seven other strains isolated in Belgium shared the same genotype with a great panel of strains isolated in China [21] and Turkey [17][34] (genotype 42). Information about the genotypes present in countries geographically located between Turkey and China is missing but this genotype 42 seems to be highly represented in the Middle East [17][35] and has already been isolated in countries like Kazakhstan [17][36].…”
Section: Discussionmentioning
confidence: 96%